Antioxidant Protection System in the Saliva of Patients with Non-Small Cell Lung Cancer - Bel’skaya, L.V.; Kosenok, V.K.; Massard, G. (Biomedical Chemistry: Research and Methods, 2019)
The purpose of the study was to study parameters of the antioxidant protection system in saliva for non-small cell lung cancer. In the case-control study, included 683 volunteers, which were divided into 3 groups: primary (lung cancer patients, n = 290), comparison group (patients with nonmalignant pulmonary pathologies, n = 178) and control (conditionally healthy individuals, n = 215). Biochemical examination of saliva, histological verification of the diagnosis were carried out for all participants. The parameters of the antioxidant defense was determined spectrophotometrically. Intergroup differences were estimated by a nonparametric criterion. Saliva of lung cancer patients was characterized by imbalance in the antioxidant defense. It is shown that the activity of the enzymes of the first link of antioxidant protection (catalase, SOD) was significantly reduced (p ˂ 0.0001), whereas activity of salivary peroxidases increase (p = 0.0037). The parameters of non-enzymatic protection varied in opposite directions: the level of uric acid in lung pathologies decreases (p = 0.0399), whereas albumin concentration increased, under these conditions, it begins to exhibit prooxidant properties. Differences between adenocarcinoma and squamous cell lung cancer have been found in terms of the mode of the dynamics of antioxidant protection parameters. Probably, against the background of squamous cell lung cancer, an enzymatic link (catalase, SOD) contributes to the antioxidant protection system, whereas against adenocarcinoma - nonenzymatic (uric acid, albumin).